2007
DOI: 10.1158/1535-7163.mct-06-0801
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed genes in radioresistant nasopharyngeal cancer cells: gp96 and GDF15

Abstract: Radiotherapy is the major treatment modality for nasopharyngeal cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 29 publications
7
63
0
2
Order By: Relevance
“…Previous studies have screened for DEPs associated with radioresistance in NPC (4,10). One study identified seven upregulated genes in radioresistant subclones of CNE2.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have screened for DEPs associated with radioresistance in NPC (4,10). One study identified seven upregulated genes in radioresistant subclones of CNE2.…”
Section: Discussionmentioning
confidence: 99%
“…11). All the cell culture conditions were the same as previously reports (9)(10)(11). The Matrigel invasion method was used to establish HNC cell sublines with a high invasive capability, similar to what has been previously described (12).…”
Section: Establishment and Characterization Of Highly Invasive Hnc Cementioning
confidence: 99%
“…The pTOPO-U6 vector was used to construct Hsp60-, GANAB-, Gp96-, and Grp78-short hairpin RNA (shRNA) plasmids as previously described (9). Briefly, a 15 to 18 sense and antisense complementary hairpin oligonucleotide was generated against a specific mRNA sequence of each gene, following cloned into pTOPO-U6 vector.…”
Section: Cloning and Transfection Of Short Hairpin Rna Plasmidsmentioning
confidence: 99%
“…Microarrays have been used to assess genes involved in radioresistance in various types of cancer (6)(7)(8)(9)(10)(11). For examples, analysis for gene expression profiles of radioresistant NPC cell lines using a cDNA array found that at least two genes, gp96 and GDF15, involved in the radioresistance of NPC cell lines (11).…”
Section: Introductionmentioning
confidence: 99%